2015
DOI: 10.1016/j.bbr.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor subunits and associated signaling molecules mediating antidepressant-related effects of NMDA-GluN2B antagonism

Abstract: Drugs targeting the glutamate N-methyl-D-aspartate receptor (NMDAR) may be efficacious for treating mood disorders, as exemplified by the rapid antidepressant effects produced by single administration of the NMDAR antagonist ketamine. Though the precise mechanisms underlying the antidepressant-related effects of NMDAR antagonism remain unclear, recent studies implicate specific NMDAR subunits, including GluN2A and GluN2B, as well as the alpha-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptor (AMPAR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…In addition, it is also reported that antidepressant effects of Ro 25–6981 were intact in mutants with global GluA1 deletion or GluN1 deletion in forebrain interneurons, but absent in mutants with global deletion of GluN2A. These findings suggest that GluN2B subtype could be a therapeutic target for depression (Kiselycznyk et al, 2015). …”
Section: Discussionmentioning
confidence: 94%
“…In addition, it is also reported that antidepressant effects of Ro 25–6981 were intact in mutants with global GluA1 deletion or GluN1 deletion in forebrain interneurons, but absent in mutants with global deletion of GluN2A. These findings suggest that GluN2B subtype could be a therapeutic target for depression (Kiselycznyk et al, 2015). …”
Section: Discussionmentioning
confidence: 94%
“…GluN2B-floxed mice were generated as previously described and backcrossed repeatedly to C57BL/6J to produce a congenic background (Brigman et al, 2010). Three separate Cre-driver transgenic lines were used to delete GluN2B in specific brain regions and neuronal subtypes when crossed with the GluN2B-floxed mice: CaMKIIα-Cre (Tsien et al, 1996) to delete GluN2B on cortical and CA1 hippocampal principal neurons (GluN2B CxNULL ) (Brigman et al, 2010), Ppp1r2-Cre (Belforte et al, 2010) to delete GluN2B on forebrain interneurons (predominantly parvalbumin-positive) (GluN2B InterNULL ) (Brigman et al, 2015; Kiselycznyk et al, 2015), and Rgs9-Cre (Dang et al, 2006) to delete GluN2B on striatal medium spiny neurons (GluN2B StNULL ) (Radke et al, 2015b) (Figure 1A). Data from the latter mutants are not reported due to insufficient numbers (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Independent of the mechanism of ketamine action, GluN2B selective antagonists exert rapid antidepressant actions in rodent models 9, 7578 . Moreover, deletion of GluN2B-containing NMDARs from pyramidal cortical neurons in the brain of mice induced an enhancement of protein synthesis and increased the number of excitatory inputs measured in the prefrontal cortex, concomitant with decreased behavioral despair in the forced-swim test and tail-suspension test, and reduced corticosterone-induced behavioral deficits 71 .…”
Section: Nmdar Inhibition-mediated Mechanismsmentioning
confidence: 99%